Catalytic cracking and catalyst deactivation/regeneration characteristics of Fe-loaded biochar catalysts for tar model compound. (15th February 2023) - Liu, Haolin; Ye, Chao; Ye, Zefu; Zhu, Zhujun; Wang, Qisong; Tang, Yuanjun; Luo, Guanqun; Guo, Wenwen; Dong, Cong; Li, Guoneng; Xu, Yousheng; Wang, Qinhui
Highlights: The toluene removal efficiency of catalyst exceeds 94%. The selectivity of H2 in tail gas can exceed 70%. Toluene and carbon deposition have a competitive relationship with iron oxides. ABC-Fe4% retains more than 66% removal efficiency after three regenerations. Abstract: The maximum toluene removal efficiency of Fe-loaded biochar was 95.36 % over a reaction time of 90 min. Carbon deposition was the leading cause of the deactivation of the catalysts. For ABC-Fe4%, the carbon yield increased with the toluene feeding time, but the rate decreased. The increase in iron concentration in the catalyst leads to a reduction in carbon yield and removal efficiency. The gas results show that H2 is the main gas produced after the reaction, with a maximum selectivity for H2 of 81.78 %. When the Fe concentration in the catalyst increases, the selectivity of CO increases from 7.61 to 23.84 %, and the corresponding H2 decreases to 65.15 %. There is competition between the toluene and the deposited carbon for the iron oxides in the catalyst; the higher the concentration of iron oxides, the easier the reaction between the catalyst and the deposited carbon. ABC-Fe4% has a reduction peak of Fe3 O4 and Fe2 O3, an acid site with a total acid amount of 1.39 mmol/g, and a more abundant oxygen-containing functional group and oxygen vacancy structure, which make it have the best removal efficiency and regenerative usability.